Gait in Controlled Ankle Movement (CAM) Walker Boot Using a Contralateral Shoe Lift - Dino Fanfan BSc; Sergio Lemus Orellana; Kyra E. Lopez MSc; Francesco Travascio PhD; Daniel Murray MD; Cary B. Chapman MD (Foot & Ankle Orthopaedics)
Category: Basic Sciences/Biologics; Other Introduction/Purpose: Walking mechanics play a fundamental role in daily mobility and are significantly influenced by footwear choices, particularly in individuals with lower limb conditions. Among the interventions commonly used in rehabilitation settings are controlled ankle movement (CAM) boots and shoe lifts, which aim to provide support and improve gait dynamics. The purpose of this outcome study was to test how different a person walks when wearing the controlled ankle movement (CAM) boot and the shoe lift compared to walking with your running shoes. Methods: We conducted a prospective cohort study comprised of 30 participants, 15 men and women, who underwent three-level walking trials under the following conditions: athletic shoes, tall CAM boot, and tall CAM boot with a balancer added to the contralateral foot. Sixteen anatomical markers were placed on participants according to Vicon’s Plug-in Gait Full Body (PIGFB) model. Kinematic data and ground reaction forces were collected at 500 Hz and processed with the PIGFB biomechanical model and Vicon’s gait cycle parameters. Data post-processing provided spatiotemporal gait parameters (contact times, stride length, speed, time spent in stance/swing phases, cadence) and lower limb kinematics and kinetics (knee and hip joint angles, movement, and forces). A Two-Way ANOVA, using walking condition and gender as factors, followed by a Tukey Pairwise comparison identified significant effects of walking conditions on various gait characteristics. Results: In both limbs, cadence (p = 0.002) and step width (p < 0.001) were significantly different in NB compared to CAM and CAMB. Specific to contralateral limb, stride time (p = 0.025), step time (p = 0.007), and limb index (p ≤ 0.001) were also affected. Regarding kinematics, the walking condition significantly affected contralateral hip abduction angle (p = 0.027). In addition, the walking condition had significant effect on the ipsilateral limb for both knee internal rotation (p = 0.024), and knee varus/adduction angle (p = 0.024). Regarding kinetics, the walking condition affected hip medial/lateral force (p =0.002), knee compression force (p =0.029), and knee varus/adduction moment (p = 0.024). The boot condition had the greatest hip force (5.7 N/kg) compared with the NB and CAMB conditions. Conclusion: Our study demonstrates significant changes in gait patterns and lower limb biomechanics when individuals wear a controlled ankle movement (CAM) boot and a shoe lift compared to athletic shoes. These results underscore the importance of considering footwear interventions in clinical and rehabilitation settings, as they can substantially influence gait patterns and biomechanical dynamics, highlighting the need for careful consideration in clinical and rehabilitation settings.